(3JaSjQ GdbQBf ddYTGHs - (3CMeO Hf eMeO Hf eaQL GdCehj CHh GdYHGS GdfHGJj GdYTGH, GHf GdQhejI,J (B637 (3g` s
(3ChdgG (B:s
(3JaSjQ ShQI Gdedc hgj ecjI HGLeGY hJSei GdhGbjI hGdefLjI s
(3BNQgG (B:s
(3ShQI GdYGOjGJ GNJdahG ajgG gd ecjI Ch eOfjI s
(3GdfSNI HgG MhGTs
(3HgG GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B218s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs